Legal Protection and Certainty of Land Rights through PTSL: A Review of Indonesian State Administrative Law - Firdaus, Kusuma; Utama, Yos Johan; Putrijanti, Aju (Journal of Posthumanism, 2025)
The Complete Systematic Land Registration (PTSL) program in Indonesia is designed to improve legal protection and certainty of land rights in Indonesia. This study employs a normative juridical research method to evaluate the regulations and execution of PTSL within the context of land administration. The results reveal that PTSL has made notable advancements in enhancing legal certainty for landowners. The analysis underscores the importance of establishing a more effective supervisory system and simplifying procedures to prevent future land disputes. To strengthen the PTSL framework, the study recommends integrating land information systems, enhancing the skills of involved personnel, and improving collaboration among relevant institutions.